Providing a Framework for Auditors’ Metacognitive Beliefs and Examining Their Impact on Ethical Decision-Making in the Auditing Profession - Fallah, Fatemeh; Khalilpour, Mehdi; Ramezani, Javad (Business, Marketing, and Finance Open, 2027)
Metacognition, as a reflective mirror through which the mind examines itself, not only represents cognitive abilities but also serves as a guiding mechanism for navigating the complexities of decision-making in professional environments. In auditing, where each judgment can be consequential, metacognitive beliefs empower auditors not only to evaluate data but also to gain insight into their own thinking processes and make ethical and well-reasoned decisions. The objective of the present study was to develop a model of auditors’ metacognitive beliefs and to examine its impact on ethical decision-making. In this study, using grounded theory and expert interviews, the components of auditors’ metacognitive beliefs were identified. In the quantitative phase, the research hypothesis was tested using structural equation modeling with SmartPLS3 software. Data on auditors’ metacognitive beliefs were collected through a researcher-developed questionnaire, and ethical decision-making was measured using a standardized questionnaire. This mixed-methods approach systematically examined the relationship between metacognitive beliefs and ethical decision-making. The qualitative findings revealed four categories (1. enhancement of auditors’ professional self-awareness, 2. professional interactions and team coordination, 3. continuous learning and professional development, and 4. professional ethics and accountability), eleven main components (including the role of self-awareness in improving audit quality, risk management in a self-aware environment, enhancement of cognitive processes in professional settings, team coordination in a self-aware environment, professional responses to criticism and feedback, interaction with emerging technologies in professional environments, and auditors’ professional development in self-aware contexts), and forty-three conceptual themes. Furthermore, the findings from the quantitative phase indicated that auditors’ metacognitive beliefs have a positive and statistically significant effect on ethical decision-making. These results can assist audit firms and standard-setters in designing supportive work environments and effective training programs to enhance audit quality and increase public trust in the profession. Ultimately, by presenting a comprehensive model, this study provides a robust foundation for future research in the domain of metacognition and professional ethics in auditing and opens new avenues for examining the complex interaction between cognition, metacognition, and ethics in professional contexts.